The late-time light curve of the Type Ia supernova SN 2011fe - Dimitriadis, G.; Sullivan, M.; Kerzendorf, W.; Ruiter, A. J.; Seitenzahl, I. R.; Taubenberger, S.; Doran, G. B.; Gal-Yam, A.; Laher, R. R.; Maguire, K.; Nugent, P.; Ofek, E. O.; et al. (Monthly notices of the Royal Astronomical Society, 2017)
Abstract We present late-time optical R-band imaging data from the Palomar Transient Factory (PTF) for the nearby Type Ia supernova SN 2011fe. The stacked PTF light curve provides densely sampled coverage down to R ≃ 22 mag over 200–620 d past explosion. Combining with literature data, we estimate the pseudo-bolometric light curve for this event from 200 to 1600 d after explosion, and constrain the likely near-infrared (Near-IR) contribution. This light curve shows a smooth decline consistent with radioactive decay, except over ∼450 to ∼600 d where the light curve appears to decrease faster than expected based on the radioactive isotopes presumed to be present, before flattening at around 600 d. We model the 200–1600 d pseudo-bolometric light curve with the luminosity generated by the radioactive decay chains of 56Ni, 57Ni and 55Co, and find it is not consistent with models that have full positron trapping and no infrared catastrophe (IRC); some additional energy escape other than optical/near-IR photons is required. However, the light curve is consistent with models that allow for positron escape (reaching 75 per cent by day 500) and/or an IRC (with 85 per cent of the flux emerging in non-optical wavelengths by day 600). The presence of the 57Ni decay chain is robustly detected, but the 55Co decay chain is not formally required, with an upper mass limit estimated at 0.014 M⊙. The measurement of the 57Ni/56Ni mass ratio is subject to significant systematic uncertainties, but all of our fits require a high ratio >0.031 (>1.3 in solar abundances).